The metaphor in hospital language - Pilar Darriba Rodríguez (Universidad de Alicante, 1999)
There are innumerable sources from which to extract metaphors but undoubtedly physical, social and cultural experiences of human beings are probably the richest fields to turn to when needed. Every 'culture' has its own language, uses its own metaphors, some of which have no significance at all in other cultures: They could be understood in a different way, they could be misinterpreted. Sometimes metaphors pad out every day language to such a point that many expressions could not be interpreted nowadays without those metaphors. Hospital life for instance, has its own vocabulary. This study tries to analyse and describe some of the metaphors used during day in day out hospital life using Lakoff and Johnson's classification.